CHANGING THE SENTSIVE CHARACTERSTICS OF THE OFFER UNDER THE INFLUENCE OF THE CONCEPT "MAN" - U.S.Yigitaliyev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
the article, problems such as changes in the meaning of the sentence under the influence of the concept "person" are studied from an anthropocentric point of view.